STATISTICAL ANALYSIS OF DYNAMIC CHARACTERISTICS ASYNCHRONOUS ELECTRIC MOTOR WITH CHANGING LOAD PARAMETERS - N. A. Malev; O. V. Pogoditsky (Известия высших учебных заведений: Проблемы энергетики)
Abstract: Research of operation electrical machines in transitional mode is an actual task. Modeling dynamic processes with changing load parameters and probabilistic assessment of simulation results allows taking into account the degree of influence of these changes on transient response. An approach to the study of the dynamics of an asynchronous electrical motor under external and parametric perturbations shown. Recommendations was given on the use of this method in solving the problem of identifying the parameters of electric machines.